2002
DOI: 10.1093/oxfordjournals.molbev.a004173
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Genome Size in Drosophila. Is the Invader's Genome Being Invaded by Transposable Elements?

Abstract: Genome size varies considerably between species, and transposable elements (TEs) are known to play an important role in this variability. However, it is far from clear whether TEs are involved in genome size differences between populations within a given species. We show here that in Drosophila melanogaster and Drosophila simulans the size of the genome varies among populations and is correlated with the TE copy number on the chromosome arms. The TEs embedded within the heterochromatin do not seem to be involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 57 publications
5
65
0
1
Order By: Relevance
“…This does not mean, however, that transposable elements play no role in accounting for the differences in genome size between individuals and between populations. The TE content clearly differs between populations and species as a result of selection, and so may be related in some way to environmental conditions (14,17). It is hard to imagine that a rapid change in TE content could be produced simply by changing the temperature at which the development of the flies takes place, the humidity of the medium, or the age of the flies, although such a possibility cannot be entirely ruled out by our experiments, and needs to be tested.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This does not mean, however, that transposable elements play no role in accounting for the differences in genome size between individuals and between populations. The TE content clearly differs between populations and species as a result of selection, and so may be related in some way to environmental conditions (14,17). It is hard to imagine that a rapid change in TE content could be produced simply by changing the temperature at which the development of the flies takes place, the humidity of the medium, or the age of the flies, although such a possibility cannot be entirely ruled out by our experiments, and needs to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclei were extracted from five heads of freshly hatched Drosophila males. The heads were crushed in a small, siliconized Eppendorf vial containing 200 L of labeling solution (0.1-g trisodium citrate, 0.01-mL Triton X100, 0.05-mg RNAse-A, water UHQ 100 mL) with 1 g/mL propidium iodide (Aldrich) (14). The tetraodon (Tetraodon nigroviridis) blood used as the internal standard (0.8 pg) for diploid genome size estimate, but used here for relative fluorescence intensity determination of the fly nuclei, was labeled first with the fluorescent dye 5-6-carboxyfluorescein diacetate succinimidyl ester (CFSE, Molecular Probes, Leiden, The Netherlands) at 2 g/mL in PBS for 15 min, at 37°C.…”
Section: Genome Size Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study of genome size in various Drosophila species (Bosco et al, 2007) concludes that there is a significant statistical difference in genome size between species, and some significant differences between strains in some species. Vieira et al (1999Vieira et al ( , 2002 have also identified genome-size differences between populations of both Drosophila melanogaster and D. simulans, but no differences between replicates of batches of flies reared in the same vial. In the Bosco et al (2007) paper, the variation in genome size was related to variation in heterochromatin composition, mostly of satellite DNA, whereas TEs were mostly involved in the Vieira et al (1999Vieira et al ( , 2002 study.…”
mentioning
confidence: 99%